Vibration characteristics and suppression measures of core in saturation core fault current limiter based on nanocrystalline materials - Jiaxin Yuan; Yu Liu; Yudong Sun; Xuzhe Li; Hang Zhou (AIP Advances)
Saturation core fault current limiter (SCFCL) stands as one of the most promising current limiting technologies. Traditional SCFCLs, utilizing silicon steel as the core material, exhibit large magnetostriction coefficients and saturation points, leading to severe vibration issues during operation that compromise equipment and system safety. To address these challenges, this paper proposes a novel topology of SCFCL based on iron-based nanocrystalline alloy materials (NSCFCL). Theoretical analysis is conducted to delve into its vibration mechanism and characteristics. Utilizing finite element analysis, a 3D transient electric-magnetic-force multiphysics coupling simulation is performed on a 220 kV NSCFCL, studying the vibration displacement and acceleration distribution characteristics under the combined influence of magnetostrictive force and Maxwell force. The simulation results align well with theoretical predictions, revealing that compared to silicon steel-based SCFCL (HSFCL), NSCFCL exhibits a 71% reduction in maximum vibration displacement and a 65% decrease in maximum vibration acceleration. These findings significantly mitigate core vibration deformation and stress, validating the effectiveness of the novel topology.